Writing for science and engineering papers, presentations, and reports - Silyn-Roberts, Heather
Are you a post-graduate student in Engineering, Science or Technology who needs to know how to:Prepare abstracts, theses and journal papersPresent your work orallyPresent a progress report to your funding bodyWould you like some guidance aimed specifically at your subject area? ... This is the book for you; a practical guide to all aspects of post-graduate documentation for Engineering, Science and Technology students, which will prove indispensable to readers. Writing for Science and Engineering will prove invaluable in all areas of research and writing due its clear, concise style. The practi.